2011
DOI: 10.3113/fai.2011.0908
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Suture Knot Prominence With Suture Button Along Distal Fibula: Technical Tip

Abstract: Level of Evidence: V, Expert Opinion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
(2 reference statements)
0
17
1
1
Order By: Relevance
“…In current review, the suture-button fixation group showed similar risk of post-operative complications with the screw fixation group. Regarding the suture-button fixation group, some literatures suggested some modifications in surgical procedure, such as a posterior short knot and/or reaming the posterior aspect of fibula which was useful to reduce the incidence rate of infection, irritation and discomfort [25, 30]. These complications existed as similar issues to the screw fixation group.…”
Section: Discussionmentioning
confidence: 99%
“…In current review, the suture-button fixation group showed similar risk of post-operative complications with the screw fixation group. Regarding the suture-button fixation group, some literatures suggested some modifications in surgical procedure, such as a posterior short knot and/or reaming the posterior aspect of fibula which was useful to reduce the incidence rate of infection, irritation and discomfort [25, 30]. These complications existed as similar issues to the screw fixation group.…”
Section: Discussionmentioning
confidence: 99%
“…In the current review it was 10% on average. Several authors have already made suggestions to lower the rate of implant irritation and subsequent removal [3, 21, 39]. In the literature on syndesmotic screw fixation this percentage is dependent on hospital protocol and is slightly over 50% on average.…”
Section: Discussionmentioning
confidence: 99%
“…3 This latter complication is the most commonly cited and can be avoided by adopting a modified surgical technique. 34 Complication rates range from 8% to 25%. 3 35 36 What is not clear from previous work is when the complications were discovered, by whom and during what process, for example by the patient at work, by the physiotherapist during rehabilitation or by the surgeon on review.…”
Section: Discussionmentioning
confidence: 99%